2020
DOI: 10.1111/jre.12730
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal status, vascular reactivity, and platelet aggregation changes in rats submitted to hypercholesterolemic diet and periodontitis

Abstract: Background and objectives: Periodontitis can corroborate with development and progression of atherosclerosis and a possible bidirectional interaction between both pathologies has been hypothesized. The aim of this work was to study the interactions between diet-induced hypercholesterolemia and ligature-induced periodontitis in Wistar rats submitted to both conditions. Material and methods: Animals were divided into four experimental groups: C (control: standard diet without periodontitis), Perio (periodontitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…Besides, it is well known that diet-induced hypercholesterolemia can result in vascular damage, especially in the endothelium, leading to impaired vascular relaxant responses and an increased response to vasoconstrictor agonists such as phenylephrine (PEN) [ 50 , 51 , 52 ]. Regarding the contractile response to FEN, vasoconstriction was potentiated in CH56 but not in CN56, showing that the consumption of hypercholesterolemic food for 16 weeks was effective in inducing functional damage to the endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it is well known that diet-induced hypercholesterolemia can result in vascular damage, especially in the endothelium, leading to impaired vascular relaxant responses and an increased response to vasoconstrictor agonists such as phenylephrine (PEN) [ 50 , 51 , 52 ]. Regarding the contractile response to FEN, vasoconstriction was potentiated in CH56 but not in CN56, showing that the consumption of hypercholesterolemic food for 16 weeks was effective in inducing functional damage to the endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…This hyperlipidemia rat model demonstrates that a high-cholesterol diet induces spontaneous alveolar bone destruction but exhibits no addictive effect on periodontitis-induced bone loss [ 186 ]. On the opposite, some other studies found that obesity/hyperlipidemia induced by high fat and hypercaloric diet act as potentiating factors for ligature-induced periodontal destruction in rats [ 187 ]. Variations of diet composition, induction methods of periodontitis and timespan of experiment probably contribute to the inconsistency between results of animal studies.…”
Section: Metabolic Disorders Of Energy Substratesmentioning
confidence: 99%
“…The pathogenesis of endothelium injury in the inflammation is complicated. The direct damaging effect of periodontal microbes on the vascular endothelium is mainly developed due to their adhesion and invasion into endothelial cells [13]. Endothelial damage leads to intra-vascular changes: platelet aggregation and the activation of coagulation [13].…”
mentioning
confidence: 99%
“…The direct damaging effect of periodontal microbes on the vascular endothelium is mainly developed due to their adhesion and invasion into endothelial cells [13]. Endothelial damage leads to intra-vascular changes: platelet aggregation and the activation of coagulation [13]. It has been also established that ET-1 was involved in the regulation of proinflammatory interleukins, especially interleukin-1b expression in gingival tissues [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation